Eptinezumab for the Prevention of Migraine: Clinical Utility, Patient Preferences and Selection – A Narrative Review - Altamura C; Brunelli N; Marcosano M; Alesina A; Fofi L; Vernieri F (Dove Medical Press, 2023)
Claudia Altamura,1,2 Nicoletta Brunelli,1,2 Marilena Marcosano,1,2 Alessandro Alesina,1,2 Luisa Fofi,1,2 Fabrizio Vernieri1,2 1Fondazione Policlinico Universitario Campus Bio-Medico, Roma, 00128, Italy; 2Unit of Headache and Neurosonology, Department of Medicine and Surgery, Università Campus Bio-Medico di Roma, Roma, ItalyCorrespondence: Claudia Altamura, Unit of Headache and Neurosonology, Department of Medicine and Surgery, Fondazione Policlinico Campus Bio-Medico, Via Alvaro del Portillo, 200, Roma, 00128, Italy, Tel +3906225411270, Fax +3906225411936, Email c.altamura@policlinicocampus.itAbstract: The new Calcitonin Gene-Related Peptide (CGRP)-targeted therapies have proven high efficacy and tolerability in episodic and chronic migraine. Eptinezumab is a humanized monoclonal antibody that selectively binds CGRP with high affinity. Eptinezumab was approved by the Food and Drug Administration on February 21st, 2020, for the preventive treatment of migraine in adults. It is administered intravenously over 30 minutes with a standard dose of 100 mg and has a T-max of 30 minutes-1 hour and a half-life of 27 days. These pharmacological properties allow for a very rapid onset of effect and a quarterly administration. It is the first time that a preventive treatment for migraine can be offered as an intravenous administration. As the range of therapeutic possibilities in migraine is expanding, the treatment process must include common decision-making, where physicians should explain in detail to patients the different characteristics of treatment options beyond efficacy and side effects. Patients can now express a preference on a range of opportunities: pharmacological versus non-pharmacological approaches, route of administration, frequency of administration, efficacy, rapidity, side effects, costs, the possibility of titration or dosing, and durability of effectiveness at suspension. Also, patient preferences can be influenced by age, country, migraine severity, and earlier experience with CGRP-targeted therapies. Besides, adherence may be influenced by several factors, including route and the schedule of administration. This narrative review describes a new perspective from the patient's point of view. Clinicians should ally with patients to select treatments that meet each patient's needs and thus apply a tailored approach, addressing not only headaches. In this way, physicians would care for the patients globally and stand out their preferences on different aspects of treatment. Besides, healthcare professionals shall be aware that patients' beliefs about therapies are subject to change with increasing experience with new therapeutic approaches.Keywords: eptinezumab, CGRP, preference, adherence